Studies of Reaction Kinetics of Methane Hydrate Dissocation in Porous Media - Moridis, George J.; Seol, Yongkoo; Kneafsey, Timothy J. (Lawrence Berkeley National Laboratory, 2005)
The objective of this study is the description of the kinetic dissociation of CH4-hydrates in porous media, and the determination of the corresponding kinetic parameters. Knowledge of the kinetic dissociation behavior of hydrates can play a critical role in the evaluation of gas production potential of gas hydrate accumulations in geologic media. We analyzed data from a sequence of tests of CH4-hydrate dissociation by means of thermal stimulation. These tests had been conducted on sand cores partially saturated with water, hydrate and CH4 gas, and contained in an x-ray-transparent aluminum pressure vessel. The pressure, volume of released gas, and temperature (at several locations within the cores) were measured. To avoid misinterpreting local changes as global processes, x-ray computed tomography scans provided accurate images of the location and movement of the reaction interface during the course of the experiments. Analysis of the data by means of inverse modeling (history matching ) provided estimates of the thermal properties and of the kinetic parameters of the hydration reaction in porous media. Comparison of the results from the hydrate-bearing porous media cores to those from pure CH4-hydrate samples provided a measure of the effect of the porous medium on the kinetic reaction. A tentative model of composite thermal conductivity of hydrate-bearing media was also developed.